Legal challenges of digital technology abuse in cybersex trafficking in Indonesia - Arsawati, Ni Nyoman Juwita (Trigin Publisher, 2025)
The rapid advancement of digital technology has transformed human trafficking into a technology-enabled crime, particularly cybersex trafficking, in which sexual exploitation is conducted entirely through online platforms without requiring physical movement of victims. In Indonesia, this phenomenon presents a serious legal challenge because existing criminal regulations have not been designed to address the digital, covert, and transnational characteristics of such crimes, resulting in inadequate protection for victims, especially children. This study employs normative legal research using legislative, conceptual, and comparative approaches by examining primary legal materials, including the ITE Law, the Anti-Trafficking Law, the Child Protection Law, and the Criminal Code, as well as secondary materials such as academic journals, international reports, and comparative regulations from Southeast Asian countries, particularly the Philippines and Thailand, published between 2015 and 2025. The analysis reveals that Indonesia’s legal framework does not explicitly criminalize cybersex trafficking as a form of trafficking in persons, causing law enforcement to rely mainly on cybercrime and pornography provisions that fail to capture the trafficking dimension inherent in online sexual exploitation. This regulatory gap perpetuates structural victimization, limits access to restitution and rehabilitation for victims, and leaves the criminal responsibility of digital platform providers insufficiently regulated. Furthermore, Indonesia’s non-ratification of the Budapest Convention on Cybercrime restricts effective cross-border cooperation and digital evidence handling. The study concludes that cybersex trafficking constitutes a distinct form of technology-enabled human trafficking that requires comprehensive legal reform, including explicit criminalization, the integration of a victim-centered justice approach, the imposition of corporate liability on digital platforms, and alignment with international cybercrime standards to ensure effective legal protection and justice in the digital era.